2016
DOI: 10.1097/wnr.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Valence processing of first impressions in the dorsomedial prefrontal cortex

Abstract: Previous studies have suggested that the dorsomedial prefrontal cortex (dmPFC) plays a central role in processing first impressions; however, little is known about how dmPFC processes different valences of first impressions. Moreover, it is still unclear as to whether the dmPFC shows lateralization or only induces different levels of activation when processing positive and negative impressions. To address these questions in the present study, the brain activities for the impression judgments expressed by parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For example, previous evidence showed that both cognitive and affective empathy-associated brain regions are more activated when people observe familiar friends than unfamiliar strangers in pain (Meyer et al, 2012 ). A number of studies further suggested that the brain regions for impression formation are highly overlapped with the areas supporting cognitive empathy (Mitchell et al, 2004 ; Schiller et al, 2009 ; Yu et al, 2016 ). According to these lines of evidence, the present opinion suggests that our prior knowledge constructs a moderated role on both the lower and higher routes.…”
Section: Hypothesized Connectionsmentioning
confidence: 99%
“…For example, previous evidence showed that both cognitive and affective empathy-associated brain regions are more activated when people observe familiar friends than unfamiliar strangers in pain (Meyer et al, 2012 ). A number of studies further suggested that the brain regions for impression formation are highly overlapped with the areas supporting cognitive empathy (Mitchell et al, 2004 ; Schiller et al, 2009 ; Yu et al, 2016 ). According to these lines of evidence, the present opinion suggests that our prior knowledge constructs a moderated role on both the lower and higher routes.…”
Section: Hypothesized Connectionsmentioning
confidence: 99%
“…Although there was a method for mass univariate analysis to obtain enough power by averaging the original number of time points to a much smaller number of time points (H.-C. Chen et al, 2011;H.-C. Chen et al, 2008;Khan, Hong, & Hong, 2014;Scholkmann, Wolf, & Wolf, 2013;B. Xu et al, 2014;Yu et al, 2016;Zimmermann et al, 2013), we argue that this method may decrease the temporal resolution due to loss of information on the neglected time points. By contrast, without losing any temporal information, MTPA was able to detect a significant difference between conditions with many time points and further led to a conclusion consistent with previous research.…”
Section: Discussionmentioning
confidence: 93%
“…Also, this choice echoed the rationale of a widely used down-sampling approach (Chen et al, 2011;Chen et al, 2008;Khan, Hong, & Hong, 2014;Scholkmann, Wolf, & Wolf, 2013;B. Xu et al, 2014;Yu et al, 2016;Zimmermann et al, 2013), which typically averages s e v er al n ei gh bo r i ng t i m e p o i n t s to a 5 H z r a t e ( Our sampling rate Bandwidth ¼ 10 Hz 2 ¼ 5 Hz ). Furthermore, implementing larger bandwidths did not provide additional benefit to constitute a significant improvement over a bandwidth of 2 in the present NIRS data set (the results of a bandwidth of 3 are also shown in Supplementary Figure 2 for demonstration purposes).…”
Section: Data Partitioning: Choosing Bandwidth To Determine the Subset Datamentioning
confidence: 98%
See 1 more Smart Citation
“…Then, the waveform was replotted so that the signal change value at the onset was 0. Based on previous fNIRS studies demonstrating significant oxy‐Hb signal changes around 10–20 s after visual stimulation (Takahashi et al, ; Yu, Wang, & Hu, ), the analysis period was set at 10–20 s after the onset of the facial photograph, and the signal changes during the analysis period were averaged and used as the indices of brain activity for the faces. The mean signal changes were examined by ANOVA.…”
Section: Methodsmentioning
confidence: 99%